PENGARUH MEDIA SOSIAL TERHADAP KETERAMPILAN BERBAHASA INDONESIA PADA GEN Z - Heni Tri Astuti; Mita Ardiana Putri; Nurlisa Nurlisa (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
The rapid development of digital technology has positioned social media as an integral part of Generation Z’s daily life, particularly through platforms such as Instagram and TikTok. The high intensity of social media use not only influences communication patterns but also affects Indonesian language skills. This study aims to analyze the impact of social media on the Indonesian language skills of Generation Z by examining language practices on Instagram and TikTok and their conformity with the General Guidelines for Indonesian Spelling (PUEBI). This research employs a library research method with a qualitative descriptive-analytical approach. Data were collected through a review of relevant literature, including academic books, national and international journal articles, and previous studies related to language use and social media. The findings indicate that social media exerts a dual impact on the Indonesian language skills of Generation Z. On the one hand, social media increases the intensity of Indonesian language use and enhances listening, speaking, reading, and writing skills in a communicative manner. On the other hand, the dominance of non-standard language, code-mixing, and abbreviations may reduce adherence to standard Indonesian language rules, particularly in academic contexts. Therefore, the strategic use of social media through language development and digital literacy education is essential to support the balanced improvement of Indonesian language skills in the digital era.